Design of experiments with MINITAB - Mathews, Paul G., 1960- (ASQ Quality Press, 2005)
Most of the classic DOE books were written before DOE software was generally available, so the technical level that they assumed was that of the engineer or scientist who had to write his or her own analysis software. In this practical introduction to DOE, guided by the capabilities of the common software packages, Paul Mathews presents the basic types and methods of designed experiments appropriate for engineers, scientists, quality engineers, and Six Sigma Black Belts and Master Black Belts. Although instructions in the use of MINITAB are detailed enough to provide effective guidance to a new MINITAB user, the book is still general enough to be very helpful to users of other DOE software packages. Every chapter contains many examples with detailed solutions including extensive output from MINITAB. Preview a sample chapter from this book along with the full table of contents by clicking here.You will need Adobe Acrobat to view this pdf file.
Keywords: Minitab.; Statistical hypothesis testing.; Experimental design.; Science -- Statistical methods.; Engineering -- Statistical methods.; elektronické knihy; electronic books